International benchmarking for acute thrombolytic therapy implementation in Australia and Japan. (July 2016) - Kawano, Hiroyuki; Levi, Christopher; Inatomi, Yuichiro; Pagram, Heather; Kerr, Erin; Bivard, Andrew; Spratt, Neil; Miteff, Ferdinand; Yonehara, Toshiro; Ando, Yukio; Parsons, Mark
Highlights: We compared process of acute stroke care between hospitals in Australia and Japan. IV-tPA treatment rates were higher in the Australian hospital. Mild stroke was more often excluded from IV-tPA treatment in the Japanese hospital. In-hospital workflow was slower in the Australian hospital. Significant differences were noted in eligibility by severity and workflow speed. Abstract: Although a wide range of strategies have been established to improve intravenous tissue plasminogen activator (IV-tPA) treatment rates, international benchmarking has not been regularly used as a systems improvement tool. We compared acute stroke codes (ASC) between two hospitals in Australia and Japan to study the activation process and potentially improve the implementation of thrombolysis. Consecutive patients who were admitted to each hospital via ASC were prospectively collected. We compared IV-tPA rates, factors contributing to exclusion from IV-tPA, and pre- and in-hospital process of care. IV-tPA treatment rates were significantly higher in the Australian hospital than in the Japanese (41% versus 25% of acute ischaemic stroke patients, p = 0.0016). In both hospitals, reasons for exclusion from IV-tPA treatment were intracerebral haemorrhage, mild symptoms, and stroke mimic. Patients with baseline National Institutes of Health Stroke Scale score ⩽5 were more likely to be excluded from IV-tPA in the Japanese hospital. Of patients treated with IV-tPA, the door-to-needle time (median, 63 versus 54 minutes, p = 0.0355) and imaging-to-needle time (34 versus 27 minutes, p = 0.0220) were longer in the Australian hospital. Through international benchmarking using cohorts captured under ASC, significant differences were noted in rates of IV-tPA treatment and workflow speed. This variation highlights opportunity to improve and areas to focus targeted practice improvement strategies.